Relationship Between Online Service Quality Dimensions and Customers' Satisfaction: A Study of Electronic Ticketing (e-Ticketing) System in Airasia Berhad - Mohd Azmi, Che Ahmad (2011)
Airline electronic ticketing (e-ticket) system is an alternative marketing strategy implemented by airline companies to serve their customers via Internet infrastructure. Most of the airline companies employ e-ticket system in order to increase business value, reduce business operating expenses, explore new customers market and increase customers' satisfaction. One of key challenges of online service is how to manage service quality, which holds a significant importance of customer satisfaction. This study was designed to examine the relationship between online service quality dimensions with AirAsia customers' satisfaction towards e-ticket system. This study was also used technology readiness dimension to investigate the moderating effect of its on relationship between online service quality dimensions and customers' satisfaction. The sample used was from 139 AirAsia customers in UUM Kuala Lumpur and the empirical data were gathered by using structured questionnaire. From five selected online service quality dimensions; functionality, efficiency, convenience, and ease of use were shown to have a strong impact on customers' satisfaction, while only privacy shown the negative impact on customers' satisfaction. Subsequently, technology readiness was found to have a strong moderating effect on the relationship between online service quality dimensions and customers' satisfaction in e-ticket system. Finally, it was also found that technology readiness has a strong and significant relationship with customers' satisfaction.